Effective Dyeing of Cotton Fibers Using Cynomorium Coccineum L. Peel Extracts: Study of the Influential Factors Using Surface Response Methodology. Issue 1 (2nd January 2021) - Sebeia, Nouha; Jabli, Mahjoub; Ghanmi, Hanen; Ghith, Adel; Saleh, Tawfik A
ABSTRACT: The current paper focuses on the use of Cynomorium Coccineum peels extract for cotton fibers dyeing in an easy and effective way without the use of mordants. Prepared extracts were analyzed using UV-visible, FT-IR spectroscopy, Total Contents both Phenolic (TPC) and Flavanoid (TFC) and their ability to reduce reactive species by the 2, 2-diphenyl-1-picrylhydrazyl radical scavenging motion experiments. The effect of the most important dyeing conditions, including dyebath pH, temperature, extract concentration, and time contact on the performance of cotton fibers dyeing was discussed. Data were assessed by the measurement of the color strength (K/S). A surface design was adopted to assess the influential factors and the interaction effects of the studied parameters. The optimal conditions for dyeing were to be: p H = 5.5, T = 72.5°C, extract concentration = 0.275% and dyeing duration = 25 min. As also observed, changing the concentration of the electrolyte NaCl, the color strength can be improved. Overall, the friendly extracted dye exhibited excellent textile dyeing characteristics with uniform morphology as proved by SEM analysis and good fastness to washing, perspiration, and rubbing.